Development of strategies for the production of biocatalysts through immobilization / co-immobilization of lipase from Pseudomonas fluorescens - Rios, Nathalia Saraiva (2019)
In this study, lipase from Pseudomonas fluorescens (PFL) was immobilized and co-immobilized by different strategies, producing a biocatalyst library able to catalyze reactions of industrial interest in some operational conditions. Agarose and magnetic nanoparticles based supports were used as support for lipase immobilization and co-immobilization. In order to produce highly active biocatalysts, the strategy of immobilization in the open-form of lipase was maintained through adsorption on hydrophobic supports (Octyl-agarose and Octyl-nanoparticles), immobilization on heterofunctional supports containing hydrophobic groups (Glyoxyl-octyl-agarose) and covalent attachment on activated support in presence of surfactants (TEOS-nanoparticles). The strategies of co-immobilization were derived of some immobilization strategies: Multilayers of PFL were derived from the immobilization of PFL by interfacial adsorption on Octyl-agarose, which one layer of PFL is immobilized over the previous to multiply the final loading capacity of the support; PFL also was co-immobilized with other lipases (RML or LU) using the hererofunctional support (Glyoxyl-octyl-agarose) to reuse the more stable lipase (PFL) after inactivation, desorption and immobilization of the least stable lipase. These co-immobilized biocatalysts catalyze enzymatic cascade reactions or catalyze reactions involving heterogeneous substrates, such as modification of oils and fats. On the other hand, biocatalysts produced by immobilization on agarose-based supports generaly are applied to catalyze soluble substrates (which the substrate can easily penetrate into the pores of the support) and biocatalysts produced by immobilization on magnetic nanoparticles-based supports generaly are applied to catalyze insoluble or large substrates, which the enzyme is immobilized on the surface of the support, enabling the contact of the lipase with the substrate.